AGROTOURISM AND ITS USE IN KAZAKHSTAN CONDITIONS: INTERNATIONAL EXPERIENCE - A.Temirova; A.Omarkozhayeva; S.Yussupova; I. Yardyakova; S. Valieva (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the importance and economic importance of agricultural tourism in agriculture, the effectiveness of raising the prestige of rural settlements.